The impact of dementia on women internationally: An integrative review. Issue 12 (1st December 2016) - Erol, Rosie; Brooker, Dawn; Peel, Elizabeth
ABSTRACT: Women are disproportionately affected by dementia, both in terms of developing dementia and becoming caregivers. We conducted an integrative review of English language literature focusing on the issues affecting women in relation to dementia from an international perspective. The majority of relevant studies were conducted in high-income countries, and none were from low-income countries. The effects of caregiving on health, well-being, and finances are greater for women; issues facing women, particularly in low- and middle-income countries, need to be better understood. Research should focus on building resilience to help people adjust and cope long term.